Ecosystem services in Urban Nature Reserves. A Case Study in the Area Metropolitan of Buenos Aires (Semiárida, 2025)
Urban Nature Reserves (UNRs) are sites considered “oases” due to their contrasting condition with their surroundings, providing regulatory, support, and recreational environmental services to surrounding communities. The objective of this research is to recognize and characterize the UNRs in the Buenos Aires Metropolitan Area (AMBA) and identify the Ecosystem Services (ES) that these reserves provide to the community. The methodology applied in the research involved a documentary analysis and fieldwork through surveys, questionnaires, and interviews. Among the results achieved, a characterization of the 20 officially declared RNUs in the AMBA has been completed, an analysis of the general problems presented by these reserves has been developed, and a preliminary analysis of the main ES provided by the reserves has been carried out, recognizing differential contributions with respect to the types of ES they provide, according to the specific characteristics of the reserves. For the analysis, a comparison was made of three of them, which constituted the sample, consisting of: the Santa Catalina Municipal Nature Reserve, the Laguna de Rocha Integral and Mixed Nature Reserve, and the “Ecoparque” Educational Nature Reserve, based on the perceptions that exist about them on the part of the community and an assessment of the types of ES provided by the reserves in the sample. In conclusion, this research contributes to recognizing the importance and diversity of the ES provided by reserves and to identifying the main management issues and challenges they face.
Keywords: Protected natural areas; conservation; preservation